2011
DOI: 10.1103/physreve.83.031915
|View full text |Cite
|
Sign up to set email alerts
|

Role of dissolved salts in thermophoresis of DNA: Lattice-Boltzmann-based simulations

Abstract: We use a lattice Boltzmann based Brownian dynamics simulation to investigate the dependence of DNA thermophoresis on its interaction with dissolved salts. We find the thermal diffusion coefficient D{T} depends on the molecule size, in contrast with previous simulations without electrostatics. The measured S{T} also depends on the Debye length. This suggests thermophoresis of DNA is influenced by the electrostatic interactions between the polymer beads and the salt ions. However, when electrostatic forces are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Many questions still remain, one of which is the dependence of thermophoresis on particle size. Practically, the characteristic of size dependent thermophoresis has a potential application for the separation of particles of different sizes [9][10][11], the manipulation of DNAs [12][13][14], and the enhancement of heat transfer of nanofluids [15][16][17][18][19][20][21][22]. In the literature, although numerous theoretical and experimental studies have been reported on the size dependence of thermophoresis for dilute polystyrene (PS) beads dispersed in aqueous solutions, the results of these investigations are inconsistent and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Many questions still remain, one of which is the dependence of thermophoresis on particle size. Practically, the characteristic of size dependent thermophoresis has a potential application for the separation of particles of different sizes [9][10][11], the manipulation of DNAs [12][13][14], and the enhancement of heat transfer of nanofluids [15][16][17][18][19][20][21][22]. In the literature, although numerous theoretical and experimental studies have been reported on the size dependence of thermophoresis for dilute polystyrene (PS) beads dispersed in aqueous solutions, the results of these investigations are inconsistent and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Due to all of these reasons, the simulation of natural convection and thermofluidic flow in cavity requires less computational cost. This promotes the application of this method for engineering problems such as energy, double diffusive convection, heating and cooling of a unit [10,11,30,31,34].…”
Section: Lattice Boltzmann Methods (Lbm)mentioning
confidence: 96%
“…Lattice Boltzmann method (LBM) is an effective numerical method for a wide range of complex fluid flow phenomena that are problematic for conventional methods [10,11,30,31]. LBM can be differentiated from other numerical methods due to the following reasons.…”
Section: Lattice Boltzmann Methods (Lbm)mentioning
confidence: 99%
“…However, until 2010, most applications of DNA origamis are remain in a concept or testing phase [14]. Researchers focus on the design of DNA origami with different shape or functions, such as DNA origami tubes [15][16], square lattice [17][18][19][20], rectangular [21][22], triangular [17,[23][24][25][26][27][28]] and so on.…”
Section: Introductionmentioning
confidence: 99%